Liderazgo directivo y desempeño docente en la Institución Educativa. “Andrés Avelino Cáceres” del distrito de Parcoy, Pataz. 2017 - Velezmoro Araujo, Jesús (2019)
ABSTRACT This study was guided to determine the relationship between management leadership and teaching performance in the Educational Institution. "Andrés Avelino Cáceres" from the district of Parcoy Pataz Province in the year 2017. It used the descriptive method, not experimental, correlacional, constituted for (48 teachers and 7 managers). The instruments must have a character of evaluation and self-evaluation: Survey of managerial leadership and survey of teaching performance, both validated in the construction and reliability. The achievements of this investigation referred in the chapter IV of the conclusions, it was obtained: 1) The level of directive leadership was in 16.4% (9) deficient, 45.5% (25) regular, 29.1% (16) good, and a 9.1% (5) excellent 2) Respect to the teaching performance, 21.8% (12) rated deficient, 43.6% (24) regular, 25.5% (14) good and 9.1% (5) excellent. 3) A statistically significant relationship was found between the variables directive leadership and teaching performance (Rho = 0.752, p = 0.00,  = 0.05) with which the main hypothesis is demonstrated. With respect to the relationship between the dimensions of both variables, an association has been found in all with a (Rho> 0.8, p = 0.00 and  = 0.05).